Health‐related quality of life in post‐infectious bronchiolitis obliterans: agreement between children and their proxy - Edgar E. Sarria; Eduardo Mundstock; Helena T. Mocelin; Gilberto B. Fischer; Renato R. Torres; João G.M. Garbin; Lisiane F. Leal; Marcia H.R. de F. Arend; Ricardo Stein; Linda Booij; Rafael M.F. de Araújo; Rita Mattiello (Brazilian Society of Pediatrics, 2019)
Objective: To assess the level of agreement in health‐related quality of life between children with Post‐infectious Bronchiolitis Obliterans and their parent (so‐called proxy). Methods: Participants aged between 8and 17 years who had been previously diagnosed with Post‐infectious Bronchiolitis Obliterans were regularly followed up at a pediatric pulmonology outpatient clinic. Parents or legal guardians (caregivers) of these patients were also recruited for the study. A validated and age‐appropriate version of the Pediatric Quality of Life Inventory 4.0 was used for the assessment of health‐related quality of life. Caregivers completed the corresponding proxy versions of the questionnaire. The correlation between self and proxy reports of health‐related quality of life was determined by intra‐class correlation coefficient and dependent t‐tests. Results: The majority of participants were males (79.4%), and the average age was 11.8 years. Intra‐class correlations between each of the Pediatric Quality of Life Inventory 4.0 domains and the total score were all lower than 0.6, with a range between 0.267 (poor) and 0.530 (fair). When the means of each domain and the total score of the questionnaires were compared, caregivers were observed to have a significantly lower health‐related quality of life score than children, with the exception of the social domain in which the difference was not significant. However, the differences in score exceeded the critical threshold difference of four points in all other domains. Conclusion: Proxies of children and adolescents with Post‐infectious Bronchiolitis Obliterans appear to consistently perceive their children as having lower health‐related quality of life than how the patients perceive themselves. Resumo: Objetivo: Avaliar o nível de concordância a respeito da qualidade de vida relacionada à saúde entre crianças com bronquiolite obliterante pós‐infecciosa e seus pais (responsáveis). Métodos: Os participantes entre 8‐17 anos, anteriormente diagnosticados com bronquiolite obliterante pós-infecciosa, foram acompanhados regularmente no ambulatório de pneumologia pediátrica. Os pais ou responsáveis legais (cuidadores) desses pacientes também foram convidados a participar do estudo. Uma versão validada e adequada para a idade do Inventário Pediátrico de Qualidade de Vida, versão 4.0, foi utilizada para a avaliação da qualidade de vida relacionada à saúde. Os cuidadores concluíram as versões do questionário correspondentes aos responsáveis. A correlação entre os autorrelatos e os relatos dos responsáveis da qualidade de vida relacionada à saúde foi determinada pelo coeficiente de correlação intraclasse e pelos testes t dependentes. Resultados: A maior parte dos participantes era do sexo masculino (79,4%) e a idade média foi 11,8 anos. As correlações intraclasse entre cada um dos domínios do Inventário Pediátrico de Qualidade de Vida e o escore total foram todas inferiores a 0,6, com intervalo entre 0,267 (baixo) e 0,530 (justo). Quando as médias de cada domínio e o escore total dos questionários foram comparados, observamos que os cuidadores apresentaram qualidade de vida relacionada à saúde significativamente menor em comparação com as crianças, com exceção do domínio social, no qual a diferença não foi significativa. Contudo, as diferenças no escore ultrapassaram o limite de diferença essencial de 4 pontos em todos os outros domínios. Conclusão: Os responsáveis pelas crianças e adolescentes com bronquiolite obliterante pós-infecciosa parecem perceber de forma consistente que suas crianças possuem qualidade de vida relacionada à saúde menor que os próprios pacientes. Keywords: Health‐related quality of life, Bronchiolitis obliterans, Children, Palavras‐chave: Qualidade de vida relacionada à saúde, Bronquiolite obliterante, Crianças